Total Thrombus-Formation System in Patients with Peripheral Artery Disease - Christian Pfrepper MD; Careen Franke MD; Michael Metze MD; Maria Weise MD; Annelie Siegemund PhD; Roland Siegemund PhD; Martin Federbusch MD; Reinhard Henschler MD; Sirak Petros MD; Manuela Konert MD (Clinical and Applied Thrombosis/Hemostasis)
The Total Thrombus-formation Analysis System (T-TAS) is an automated device using coated microchips to assess thrombus formation under flow conditions. Its value to monitor coagulation function in patients under antiplatelet therapy awaits further clarification. This study evaluated T-TAS to detect response to dual antiplatelet therapy (DAPT) in patients with peripheral artery disease (PAD). T-TAS using the platelet-chip (PL-chip) and atheroma-chip (AR-chip) was performed in 60 patients with PAD on the day after lower extremity revascularization. Results were compared with light transmission aggregometry (LTA) and multiple electrode aggregometry (MEA, ADP- and ASPI-test). To determine T-TAS reference ranges, 30 healthy blood donors were enrolled. The area under the curve of the PL-chip (AUC-PL) was outside the reference range in 91.2% and AUC-AR in 21.1% of the PAD patients. Low responders in MEA ASPI, MEA ADP or both tests and low responders in LTA induced by ADP had a significantly higher AUC-PL compared to responders (204 vs 70, p = .016 and 140 vs 32, p < .001), respectively. Median AUC-PL in low responders in LTA and MEA, LTA or MEA and in responders in LTA and MEA was 301, 104 and 32 (p = .001), respectively. Our results suggest that the PL-chip can continuously assess the level of response to DAPT and might be helpful to monitor PAD patients.